Canonical morphology and syntax - Brown, Dunstan; Chumakina, Marina; Corbett, Greville G. (Oxford : Oxford University Press, 2012)
This book presents canonical typology, a framework for comparing constructions and categories across languages. The canonical method takes the criteria used to define particular categories or phenomena (eg negation, finiteness, possession) to create a multidimensional space in which language-specific instances can be placed.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syntax; Grammar, Comparative and general -- Morphology